PERANCANGAN APLIKASI PENGELOLAAN JADWAL KURSUS BERBASIS WEB PADA VIRTUOSO MUSIC CENTER - Lina; Stefi Lauren; Jeanny Pragantha; Wasino (Jurnal Serina Abdimas, 2026)
Virtuoso Music Center is a non-formal educational institution offering various tutoring programs, including music and Mandarin, aimed at supporting the development of students' interests, talents, and academic abilities. As the number of students increases, the complexity of scheduling and administration becomes increasingly complex. Currently, the process of scheduling lessons, recording student attendance, and managing fee billing is still done manually by administrators. This manual process creates various problems, including the possibility of class schedule conflicts, difficulty in monitoring student attendance, delays in the payment billing process, and difficulties in tracking student payment status. Based on these problems, this Community Service (PKM) activity was carried out with the aim of developing a web-based course scheduling and fee billing application to help make the administrative process at Virtuoso Music Center more efficient, accurate, and integrated. In addition, user accounts were also detailed so that there are several levels of administrators with different roles. The application design was carried out using the Waterfall methodology, the PHP programming language, and the MySQL database, and utilized the Bootstrap framework to produce a responsive and easy-to-use user interface. The application development concept began with interviews with partners' needs, collection of Virtuoso Music Center's historical data along with related photos, documentation related to partner data and operational activities, analysis of the partner's desired application needs, application development, application testing by partners, and finally application implementation by the PKM implementation team. Virtuoso Music Center merupakan lembaga pendidikan nonformal yang menyediakan berbagai program les, seperti musik dan bahasa Mandarin, dengan tujuan mendukung pengembangan minat, bakat, serta kemampuan akademik siswa. Seiring dengan meningkatnya jumlah peserta didik, kompleksitas pengelolaan jadwal dan administrasi semakin tinggi. Saat ini, proses pengaturan jadwal les, pencatatan kehadiran siswa, serta pengelolaan penagihan biaya masih dilakukan secara manual oleh administrator. Proses manual tersebut menimbulkan berbagai permasalahan, antara lain kemungkinan terjadinya jadwal kelas yang bertabrakan, kesulitan dalam memantau kehadiran siswa, keterlambatan dalam proses penagihan pembayaran, serta kesulitan dalam melakukan pelacakan status pembayaran dari siswa. Berdasarkan permasalahan tersebut, kegiatan Pengabdian Kepada Masyarakat (PKM) ini dilakukan dengan tujuan mengembangkan aplikasi penjadwalan dan penagihan biaya kursus berbasis web untuk membantu proses administrasi di Virtuoso Music Center agar lebih efisien, akurat, dan terintegrasi. Selain itu, akun pengguna juga diperinci sehingga terdapat beberapa tingkatan pengelola yang memiliki peran yang berbeda. Perancangan aplikasi dilakukan dengan menggunakan metodologi Waterfall, bahasa pemrograman PHP, serta basis data MySQL, dan memanfaatkan framework Bootstrap untuk menghasilkan antarmuka pengguna yang responsif dan mudah digunakan. Konsep pengembangan aplikasi dimulai dengan wawancara kebutuhan mitra, pengumpulan data sejarah Virtuoso Music Center beserta foto terkait, dokumentasi terkait data dan kegiatan operasional mitra, analisis terhadap kebutuhan aplikasi yang diinginkan mitra, pembuatan aplikasi, pengujian aplikasi oleh mitra, hingga akhirnya implementasi aplikasi oleh tim pelaksana PKM.